Locational Drivers of China’s Digital Creative Industries: Unveiling Regional Concentration and Sectoral Differences - Xiaoyi Luo; Ni Gao; Xiaoming Yuan (Journal of Theoretical and Applied Electronic Commerce Research, 2025)
The digital creative industry (DCI) has become an integral part of China’s strategic emerging industries. This paper, utilizing county-level data from Chinese digital creative enterprises in 2022, examines the locational factors influencing the spatial distribution of China’s DCI through Principal Component Analysis and Multiple Linear Regression Analysis. The findings indicate that technological innovation and the level of economic development universally and dominantly influence the agglomeration of all DCI sub-sectors. Service-oriented digital creative enterprises are more likely to cluster in areas with abundant cultural resources and public facilities, with government policies and financial subsidies playing a significant role. In contrast, digital creative equipment manufacturing companies are more likely to locate in proximity to market demand and related industries.